Knowledge acquisition and its relationship to the level of performance of some scouting skills among female students of the College of Physical Education and Sports Sciences at the University of Sulaimani - Kaka, Asst.L.Sheheryar Faisal; Abdullah, Asst.L.Rajan Hassan; Suleiman, Asst.L.Hiwa Mohammed Ali (Sulaimani Journal for Humanities, 2026)
This research aims to identify the level of certain scouting skills among female students at the College of Physical Education and Sports Sciences, University of Sulaimani, and to determine the relationship between academic achievement and the level of these scouting skills. The researchers employed a descriptive correlational approach, appropriate to the nature of the research problem. A purposive sample of 30 third-year female students from the College of Physical Education and Sports Sciences, University of Sulaimani, was selected for the 2022-2023 academic year. The researchers utilized various data collection tools and equipment. After analyzing the results, the Statistical Package for the Social Sciences (SPSS) was used. The study revealed a positive correlation between academic achievement and scouting skills among the female students, indicating that students with higher academic achievement possess better scouting skills. The researchers recommend strengthening the academic component related to scouting skills in the curriculum by updating the theoretical content to align with practical application